STRATEGI PENGELOLAAN KEUANGAN PERUSAHAN PADA PT GUNUNG RAJA PAKSI TBK UNTUK MENINGKATKAN KINERJA KEUANGAN - Husnah, Rira Ayatul; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the financial management strategies implemented by PT Gunung Raja Paksi Tbk in improving the company’s financial performance. The research employs a descriptive qualitative method using secondary data obtained from the company’s financial statements for the period 2020–2025, sourced from official publications. Data collection was conducted through documentation studies, while data analysis utilized financial ratio analysis, including liquidity, solvency, activity, and profitability ratios. The results indicate that PT Gunung Raja Paksi Tbk experienced a significant improvement in financial performance during the study period. This is reflected in the increasing liquidity ratios, which show the company’s enhanced ability to meet its short-term obligations, and the decreasing solvency ratios, indicating a healthier capital structure with reduced dependence on debt. Furthermore, the improvement in activity ratios demonstrates more efficient utilization of assets in generating revenue, while the rising profitability ratios indicate the company’s success in increasing profits through effective cost management and revenue optimization. Overall, the study concludes that integrated and sustainable financial management strategies have a strong relationship with the improvement of the company’s financial performance. This research is expected to provide valuable insights for company management in making effective financial decisions and serve as a reference for future studies in the field of financial management.